Grit and motivation for learning English among Japanese university students. (February 2021) - Chen, Xinjie; Lake, J.; Padilla, Amado M.
Abstract: This study contributes to the limited research assessing how constructs (e.g., grit) from Positive Psychology (PosPsy) can contribute to better understanding motivation for learning a second language (L2). A total number of 441 Japanese female university students enrolled in English language classes participated in this study. Results showed that a positive global self-construct (i.e., grit), positive L2 domain self-constructs (i.e., grit for L2 learning and interested L2 self) and positive L2 motivational constructs (i.e., L2 reading and listening self-efficacy) and negative L2 motivational variables (i.e., L2 reading and listening anxiety) can be reliably measured with self-report scales with female Japanese students and how the relationship strength among variables followed the predicted order. This paper contributes by introducing new concepts from PosPsy to motivation in L2 learning and offers validation evidence that scales can be created to measure selected constructs from PosPsy that augment L2 motivation studies.